Post-COVID learning loss and the collapse of the education-economy link in Bulgaria - Rusinov, Stoycho; Sokolova, Nadya (Society and Economy in Central and Eastern Europe, 2026)
This study examines how the COVID-19 pandemic affected the relationship between educational outcomes and regional economic indicators in Bulgaria and the Central and Eastern European (CEE) region. Using panel data from all 28 Bulgarian Nomenclature of Territorial Units of Statistics (NUTS) 3 regions between 2015 and 2024, we analyse weighted matriculation exam scores in con-junction with macroeconomic variables, including Gross Domestic Product per capita, internet access and share of educated population. The post-pandemic learning loss weakened the previously strong correlation between regional economic wealth and academic achievement, exposing structural inequalities. We find limited evidence that digital infrastructure improved outcomes, especially in marginalised regions. Furthermore, our findings indicate a persistent learning loss following the COVID-19 pandemic, with exam performance declining by up to 0.29 points (approximately 0.38 to 0.447 standard deviations) in 2021–2022, followed by a full recovery in 2024. We argue that learning losses were already happening before COVID-19, with an average magnitude of 0.01–0.03 standard deviations, with some years reaching as much as 0.1 standard deviations.